Patterns of and Rationale for the Co-use of Methamphetamine and Opioids: Findings From Qualitative Interviews in New Mexico and Nevada - Rhed, Brittany D.; Harding, Robert W.; Marks, Charles; Wagner, Katherine T.; Fiuty, Phillip; Page, Kimberly; Wagner, Karla D. (Frontiers in Psychiatry, 2022)
Introduction: Methamphetamine use and methamphetamine-involved deaths have increased dramatically since 2015, and opioid-related deaths now frequently involve methamphetamine. Nevada and New Mexico are states with elevated rates of opioid and methamphetamine use. In this paper, we report results from a qualitative analysis that examined patterns of methamphetamine and opioid co-use over participants’ lifespan, factors that influence those patterns, and implications for health outcomes among users. Methods: Project AMPED was a multisite, mixed-methods study of methamphetamine use in Northern New Mexico and Northern Nevada. Between December 2019 and May 2020, qualitative interview participants were asked to describe their patterns of and reasons for co-administration of opioids and methamphetamine. Results: We interviewed 21 people who reported using methamphetamine in the past 3 months. Four primary patterns of methamphetamine and opioid co-use were identified: (1) using both methamphetamine and heroin, either simultaneously or sequentially (n= 12), (2) using methamphetamine along with methadone (n=4), (3) using prescription opioids and methamphetamine (n=1), and using only methamphetamine (n=4). Among those who used methamphetamine and heroin simultaneously or sequentially, motivations drew from a desire to enhance the effect of one drug or another, to feel the “up and down” of the “perfect ratio” of a goofball, or to mitigate unwanted effects of one or the other. Among those who used methamphetamine and methadone, motivations focused on alleviating the sedative effects of methadone. Conclusion: To address the emergent trend of increasing methamphetamine-related deaths, researchers, health care professionals, and community health workers must acknowledge the decision-making processes behind co-use of opioids and methamphetamine, including the perceived benefits and harms of co-use. There is an urgent need to address underlying issues associated with drug use-related harms, and to design interventions and models of treatment that holistically address participants’ concerns.